Bayesian modeling identifies PLAG1 as a key regulator of proliferation and survival in rhabdomyosarcoma cells - Zheng, Yanbin (Mol Cancer Res, 2019)
We recently developed a novel computational algorithm that incorporates Bayesian methodology to identify rhabdomyosarcoma (RMS) disease genes whose expression level correlates with copy-number variations, and we identified PLAG1 as a candidate oncogenic driver. Although PLAG1 has been shown to contribute to other type of cancers, its role in RMS has not been elucidated. We observed that PLAG1 mRNA is highly expressed in RMS and is associated with PLAG1 gene copy-number gain. Knockdown of PLAG1 dramatically decreased cell accumulation and induced apoptosis in RMS cells, whereas its ectopic expression increased cell accumulation in vitro and as a xenograft and promoted G(1) to S phase cell cycle progression. We found that PLAG1 regulates IGF2 expression and influences AKT and MAPK pathways in RMS, and IGF2 partially rescues cell death triggered by PLAG1 knockdown. The expression level of PLAG1 correlated with the IC(50) of RMS cells to BMS754807, an IGF receptor inhibitor.